Study of experimentally infected cattle and sheep sensitivity to lumpy skin disease - M. S. Kukushkina; O. A. Ryabikina; A. V. Kononov; V. I. Diev (Ветеринария сегодня)
The paper presents the study results of sensitivity to lumpy skin disease virus of cattle and sheep experimentally infected with "E-95" virulent strain. It was established that cattle is more sensitive to LSDV in comparison to sheep: the disease in cattle was severe with fever, anorexia, cachexia and nodule development. Sheep reacted to virus inoculation with the development of nodules and swelling in the site of virus suspension injection, conjunctivitis, short-term anorexia and fever during 3-5 days post infection. The disease specificity was confirmed by PCR and prolonged complement fixation test.